Computed Tomography, Clinical Findings and Outcomes of Acute Anconeal Process Osteophyte Fractures and Fissures in Nine Dogs - Deards, Emma L.; Bright, Steve; Keeley, Ben; Pettitt, Rob; McConnell, James Fraser (Veterinary and Comparative Orthopaedics and Traumatology, 2025)
This study aimed to describe the clinical features, computed tomography findings and treatment outcomes of anconeal process osteophyte fractures in dogs.This was a retrospective case series. Dogs with osteoarthritis due to pre-existing elbow dysplasia or elbow fracture diagnoses, which were presented for acute/subacute elbow pain due to acute fracture of anconeal osteophytes. Diagnosis was based on computed tomographic findings. Information on the diagnostic imaging findings and treatment outcomes was documented.Nine dogs were diagnosed with anconeal process osteophyte fractures that were managed conservatively. Six of the dogs improved following conservative management and did not require surgical intervention.Anconeal process osteophyte fractures have not been previously described in dogs. Recognition of and suitable diagnostic imaging selection for this condition can lead to prompt diagnosis and appropriate case management for these patients.
Keywords: osteophyte; elbow dysplasia; osteophyte fracture; anconeal process; computed tomography